Fingolimod real life experience in non-naive multiple sclerosis patients - Sarıdaş, Furkan; Koç, Emine Rabia; Özkaya, Güven; Turan, Ömer Faruk (The European Research Journal, 2024)
Objectives: Fingolimod is approved in Turkey or the treatment of cases of multiple sclerosis (MS) which cannot be controlled with first-line treatments. There is limited information about its efficacy and safety in clinical practice in Turkey. The aim of this study was to evaluate the efficacy and safety of fingolimod treatment in patients with relapsing-remitting multiple sclerosis who were prescribed fingolimod by the Multiple Sclerosis specialists of Bursa Uludağ University Department of Neurology. Methods: This is a single-center observational study evaluating 142 patients using fingolimod who were followed up for at least 12 months in our center between April 2015 and October 2022. Efficacy results were evaluated in terms of mean number of attacks, annualized relapse rate, relapse-free patient rate, disease progression, clinical and radiological disease activity, and no evidence of disease activity (NEDA-3). The safety outcomes are the rates of treatment-related severe adverse events and patients’ continuation rates. Results: Over 12 months of treatment with fingolimod, the average number of attacks decreased by 94.6%, the annual relapse rate decreased by 87%, and most patients did not relapse (83.1%). Alongside this, in 76.4% of cases, there was no disability progression and in 83.3% of cases, magnetic resonance imaging (MRI) activation was not observed. Excluding replacement due to ineffectiveness, 89.4% of patients continued fingolimod therapy. Cardiac events, treatment-related infections and a decreased lymphocyte count were observed as side effects. Conclusion: In our center, switching from first-line treatments to fingolimod was effective in reducing disease activity in patients with multiple sclerosis.